Dividend Policies in an Unregulated Market: The London Stock Exchange, 1895—1905 - Braggion, Fabio; Moore, Lyndon (Review of Financial Studies, 2011)
[Miller and Modigliani (1961) show that in perfect and complete financial markets a firm's value is unaffected by its dividend policy. Much of the more recent research has demonstrated that dividend policy becomes important in the presence of taxation, asymmetric information, incomplete contracts, institutional constraints, and transaction costs. By examining the effects of dividend policies on 475 British firms existing between 1895 and 1905, and consequently operating in an environment of very low taxation with an absence of institutional constraints, we find strong support for asymmetric information theories of dividend policy, and little support for agency models.]